PENGEMBANGAN MODUL KIMIA MATERI STRUKTUR ATOM TERINTEGRASI NILAI-NILAI ISLAM BERBANTUAN QUICK RESPONSE (QR)-CODE - Fitriyenni, Srigustia; Kadir, Kadir; Askar, Romlah Abubakar (Dharmas Education Journal (DE_Journal), 2023)
This study aims to develop an atomic structure module integrated with Islamic values ​​with the help of Quick Response (QR)-Code to improve students' chemical literacy skills. This research departs from the problem that there are not many chemistry teaching materials that are integrated with Islamic values. This research is Research and Development (R & D) with a combination design of Defining, Designing, Developing, Dissemination (4D) and Four Steps Teaching Material Development (4 STMD). Data collection uses tests, questionnaires, and documents. The data analysis technique used is descriptive qualitative and quantitative descriptive analysis. The results of the study revealed that: 1) The feasibility of the material was declared valid (100%) based on expert judgment. Concept understanding is 84% ​​or high category. 2) The resulting module has a feasibility percentage from the results of expert validation of 91.87% 3) There is an increase in students' chemical literacy skills between the pre-test and post-test (t = -3.033; df = 34; p = 0.005). 4) Student response to the use of the atomic chemistry integration module and Islamic values ​​is 89.69% or very good. The results of this study are that the developed module has eligibility in terms of validity and practicality so that it can be implemented to improve students' chemical literacy abilities.